Seroreactivity against Helicobacter pylori VacA,50kDa and 30kDa along with alarm features may improve the diagnostic approach to uninvestigated dyspepsia: A pilot study - Manojlović Nebojša; Tufegdžić Ivana; Ristanović Elizabeta; Bokonjić Dubravko (Vojnosanitetski Pregled)
Background/Aim. Alarm features (AF) are of limited utility in predicting endoscopic findings, and the majority of patients with uninvestigated dyspepsia will have no organic pathology identified at upper gastrointestinal endoscopy. In our previous study, we highlighted seroreactivity against Helicobacter pylori (HP) antigens VacA, 50 kDa, and 30 kDa as biomarkers for gastric cancer, peptic ulcers, and functional dyspepsia. We designed and conducted this pi-lot study in order to compare the diagnostic utility of seroreactivity against HP VacA, 50 kDa, and 30 kDa with AF and investigate the possibility and adequacy of its synchronous application. Method. A careful history and physical examination with special attention to AF, esophagogastroduodenoscopy with biopsy, abdominal ultra-sound or computer tomography, complete blood count (CBC) and blood biochemistry, a Western Blot IgG against HP antigens VacA, 50 kDa, and 30 kDa, were per-formed in 123 patients with dyspepsia: 31 with gastric cancer, 31 with duodenal ulcer, 31 with gastric ulcer, and 30 with gastritis and functional dyspepsia. AF vs various combinations of seroreactivity against HP VacA, 50 kDa, and 30 kDa in patients with functional dyspepsia and others were analyzed in this study. Synchronous and alternative seroreactivity against VacA, 50 kDa, and 30 kDa, along with/without AF in patients with functional dyspepsia and other groups of patients were also analyzed. Results. VacA and 50 kDa seropositivity or AF had excellent case-findings clinical utility index for investigating dyspepsia. The absence of AF and seroreactivity against VacA either with: 50 kDa or 30 kDa seropositivity or 50 kDa and 30 kDa seropositivity had an excellent screening clinical utility index for investigating dyspepsia. Conclusion. Se-roreactivity against HP antigens VacA, 50 kDa, and 30 kDa might improve our approach to patients in investigating dyspepsia if used along with AF.